Circulating microRNAs are upregulated following acute aerobic exercise in obese individuals - Bao, Fanchen; Slusher, Aaron L.; Whitehurst, Michael; Huang, Chun-Jung (Physiology & behavior, 2018)
MicroRNAs (miRNAs), a class of non-coding RNAs, are involved in the regulation of gene expression and numerous biological processes, including inflammation and metabolism in obese populations. Emerging research indicates that physical activity provides health-related benefits in obesity-associated inflammatory diseases. This study examined how acute aerobic exercise would mediate the changes in plasma level of inflammation-related circulating miRNA (ci-miRNA) expression (miR-21, miR-126, miR-130b, miR-221, and miR-222) in obese and normal-weight subjects. Twenty-four subjects (12 obese and 12 normal-weight) were recruited to participate in a 30-min aerobic exercise (75% VO2max). Blood samples were taken prior to exercise, immediately following exercise, 1 h, and 2 h into recovery for analysis of target ci-miRNAs in plasma. A higher baseline levels of ci-miRNAs (miR-126, miR-130b, miR-221, and miR-222) were found in obese subjects than normal-weight subjects. In response to acute aerobic exercise, obese subjects exhibited a higher increase in plasma level of all ci-miRNAs: miR-21, miR-126, miR-130b, miR-221 and miR-222, even after controlling for VO2max and insulin resistance (HOMA-IR). Furthermore, all miRNA area-under-the curves “with respect to increase” (AUCi) were higher in obese subjects and also positively correlated with each other, even after controlling for VO2max and HOMA-IR. These findings indicate that acute aerobic exercise elicits a higher elevation in plasma level of inflammatory ci-miRNAs in obese than normal-weight individuals, irrespective of cardiorespiratory fitness and indicator of metabolic syndrome (HOMA-IR). •Acute aerobic exercise up-regulates inflammation-associated ci-miRNAs in obesity.•Up-regulation of target ci-miRNAs is positively correlated with each other.•ci-miRNAs might have the potential to predict the effectiveness of exercise treatment in obese Individuals.